A new neolignan, and the cytotoxic and anti-HIV-1 activities of constituents from the roots of Dasymaschalon sootepense - Sakchai Hongthong (2018)
Bioassay-guided isolation from the ethyl acetate extract of Dasymaschalon sootepense roots led to the isolation of twelve compounds including a new dihydrobenzo-furan neolignan, (+)-(2S, 3S)-2, 3-dihydro-2-(3, 4-dimethoxyphenyl)-3-methylbenzofuran-5-carbaldehyde (5), and eleven known compounds (1-4, and 6-12). The chemical structures and stereochemistry of all the isolated compounds were established by spectroscopic techniques. The known compounds 4 and 6 have been fully characterized spectroscopically, including their absolute configurations. Cytotoxic and anti-HIV-1 reverse transcriptase (RT) activities of compounds 1-3, 5 and 8-12 were determined. Among compounds screened, compounds 2, 3 and 10 displayed weak cytotoxic activity with ED50values ranging from 9.6-47.5 μM and only compound 2 was found weakly active against HIV-1 RT with an IC50 value of 323.2 μM.